ANALYSIS OF THE LEVEL OF DEMAND FOR WORK IN BIREUEN DISTRICT - Ramadhan Razali; Fuadi; Arliansyah; Rahmaniar; Rico Nur Ilham (RADJA PUBLIKA, 2023)
In Indonesia, the Open Unemployment Rate (TPT) often occurs which describes the condition of the level of demand for work. The level of demand for work is influenced by several factors such as the wage factor, the level of education completed and the factor of technological development. To overcome the open unemployment rate, the government needs to facilitate access education and skills training needed by job seekers. Research in this journal uses qualitative research methods. Using secondary data sourced from BPS Bireuen Regency in 2017-2019. This research aims to see how the influence of wage factors, recent education levels and technological developments on the level of demand for work and also on the level of open unemployment. Based on this research, it can be seen that the factor of wages, the level of recent education and technological developments have a positive influence on the level of demand for work